IMPLIKASI SURAT KEPUTUSAN MENPERINDAG NOMOR 144/MPP/KEP/4/1999 TERHADAP PERTAMBANGAN TIMAH ILEGAL DI KEPULAUANA BANGKA - Safitri Indri Ningsih (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2023)
Illegal tin mining has become increasingly widespread since the issuance of the Decree of the Minister of Industry and Trade number 144/MPP/Kep/4/1999 dated 22 April 1999 that tin is categorized as free goods (unsupervised) and the revocation of tin's status as a strategic commodity, so that it is no longer monopolized by one BUMN and can be freely exported by anyone. With the Minister of Industry and Trade Decree, of course, this has led to rampant illegal tin mining activities, so it is felt that the Government needs to create several laws and regulations as an effort to anticipate violations and criminal acts in the mining sector, tin mining in particular. The regulation that has been made by the Provincial Government of the Bangka Belitung Islands in the context of tackling illegal tin mining is Regional Regulation No. 7 of 2014 concerning Management of Mineral Mining